Sustaining diabetes prevention and care interventions: A multiple case study of translational research projects. (August 2017) - Garst, J.; L'Heveder, R.; Siminerio, L.M.; Motala, A.A.; Gabbay, R.A.; Chaney, D.; Cavan, D.
Highlights: Sustaining outcomes of healthcare interventions is crucial for diabetes prevention. Three sustainability goals: sustaining at site; diffusion to community; replication. Recommendation: choose appropriate activities for selected sustainability goal. Abstract: Background: This study identifies the barriers and enablers for sustainability of interventions in primary and secondary prevention of diabetes. In the context of translational research, sustainability is defined as the continued use of program components and activities for the continued achievement of desirable program and population outcomes. Methods: In this study, eleven translational research projects, supported by the BRIDGES program of the International Diabetes Federation, were investigated. By theoretically-informed semi-structured interviews and analyses of project reports, qualitative data was collected on the sustainability outcomes and the barriers and enablers. Results: The sustainability outcomes can be grouped in three main areas: (1) sustainability at the intervention site(s); (2) diffusion to the wider community; and (3) replication of the intervention at other site(s). Each of the outcomes has their own set of enablers and barriers, and thus requires consideration for a different sustainability strategy. Conclusions: This study is the first international study that relates the sustainability outcomes of translational research project to specific barriers and enablers, and develops an evidence-based framework which provides practical advice on how to ensure the sustainability of health interventions.